2016
DOI: 10.1097/cco.0000000000000245
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting robotic approaches to endocrine neoplasia

Abstract: Robotic endocrine procedures still play a pivotal role in minimally invasive endocrine surgery with demonstrable safety and effectiveness. Future research should embark on prospective randomized-controlled trials on robotic endocrine procedures to collect higher level of evidence and long-term survival data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…Recently, intraoperative nerve monitoring [ 38 – 41 ], a transoral approach [ 42 – 46 ], and robotic surgery [ 47 50 ] have emerged in endoscopic thyroid surgery. We believe that intraoperative nerve monitoring is efficient for identifying and preserving the recurrent nerve and external branch of the superior laryngeal nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, intraoperative nerve monitoring [ 38 – 41 ], a transoral approach [ 42 – 46 ], and robotic surgery [ 47 50 ] have emerged in endoscopic thyroid surgery. We believe that intraoperative nerve monitoring is efficient for identifying and preserving the recurrent nerve and external branch of the superior laryngeal nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the oncological safety, robotic procedures for thyroid cancers are controversial. [ 17 18 19 20 21 ] Papillary thyroid microcarcinoma has a very good prognosis. Some studies had reported that total thyroidectomy with prophylactic central lymph node dissection is necessary in patients with papillary thyroid microcarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of brachial plexus injury has since been reduced by placing the arm in a flexed 90-degree position (extended salute position), which reduces the traction on the nerve [56, 57]. Rare complications of tracheal and oesophageal injuries have been reported; however, the incidence is no higher than the conventional open approach [58].…”
Section: Robotic Transaxillary Thyroidectomymentioning
confidence: 99%